Variation in the VLF signal noise amplitude during the period of intense seismic activity in Central Italy from 25 October to 3 November 2016 - Nina, Aleksandra; Biagi, Pier Francesco; Pulinets, Sergey; Nico, Giovanni; Mitrović, Srđan T.; Čadež, Vladimir M.; Radovanović, Milan; Urošev, Marko; Popović, Luka Č. (Frontiers in Environmental Science, 2022)
Recent research shows reductions in the VLF signal noise amplitude that begin before particular earthquakes whose epicentres are more than 100 km away from the signal propagation path. In this paper, we extend this research to studying the noise amplitude during periods of intense seismic activity in a localized area. We analyse variations in the VLF signal noise amplitude over a period of 10 days (25 October - 3 November 2016) when 981 earthquakes with the minimum magnitude of 2 occurred in Central Italy. Out of these events, 31 had the magnitude equal or greater than 4, while the strongest one had the magnitude of 6.5. We observe the VLF signal emitted by the ICV transmitter located in Sardinia (Italy) and recorded in Belgrade (Serbia). Bearing in mind that the trajectory of this signal crosses the area in which the observed earthquakes occurred, we extend the existing research to study of variations in the noise amplitude of the signal propagating at short distances from the epicentres of the considered earthquakes. In addition, we analyse the impact of a large number earthquakes on characteristics of the noise amplitude and its reductions before particular events. In order to examine the localization of the recorded changes, we additionally analysed the noise amplitude of {\color{red} two} reference signals emitted in {\color{red} Germany and} Norway. The obtained results show the existence of the noise amplitude reduction preceding individual strong or relatively strong earthquakes, and earthquakes followed by others that occurred in a shorter time interval. However, the additional noise amplitude reductions are either not pronounced or they do not exist before the considered events in periods of the reduced noise amplitude remain from previous earthquakes. Reductions in noise amplitudes for all observed signals indicate a larger perturbed area through which they spread or its closer location to the receiver. The analysis of daily values of parameters describing the noise amplitude reveals their variations start up to two weeks before the seismically active period occurs.